Analisis Strategi Pemasaran UMKM Cendol Sonia dalam Meningkatkan Volume Penjualan di Denpasar - Aulya Rahman Adi Luhung; Ni Made Hartini (Journal Research of Management, 2024)
This study aims to determine the marketing strategy used by UMKM Cendol Sonia in increasing sales volume. The data analysis technique used in this study is a descriptive analysis technique using SWOT analysis. The data analysis method used in this research is descriptive with a qualitative approach. The method used is to analyze the internal environment (strengths and weaknesses) and external (opportunities and threats). Based on the results of research on marketing strategy analysis in increasing sales volume of UMKM Cendol Sonia using SWOT analysis it shows that the company is in quadrant I which supports aggressive growth policies (growth oriented), this can be seen from IFAS with a score of 3.67 and EFAS with a score 3.51. To increase the sales volume of UMKM Cendol Sonia, they can implement Market Development, Market Penetration and Product Development.